Compositional fuzzy modeling of energy- and resource saving in socio-technical systems - Bobryakov, A. V.; Borisov, V. V.; Gavrilov, A. I.; Tikhonova, E. A. (EAI Endorsed Transactions on Energy Web, 2018)
The paper poses the problem of increasing the efficiency of energy- and resource saving in socio-technical systems, which consist of resource-intensive subsystems (for example, subsystems of electricity, heat and water supply). A compositional fuzzy model for efficiency estimating of energy- and resource saving of socio-technical systems is proposed. This compositional fuzzy model consists of the following models: firstly, a set of fuzzy cognitive models for estimating the effects of actions on the subsystems’ indicators; secondly, a set of fuzzy rules-based models for efficiency estimating of energy- and resource saving of subsystems; thirdly, a generalized fuzzy model for efficiency estimating of energy- and resource saving of system as a whole. The procedure of compositional fuzzy modeling of energy- and resource saving in socio-technical systems is described.